PENGARUH UKURAN PERUSAHAAN DAN KEPEMILIKAN MANAJERIAL TERHADAP PENGUNGKAPAN LAPORAN KEUANGAN - Dien Sefty; IFTAHUL FARIHAH (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2016)
The purpose of this study was to analyze the variables that Influence the size of the company and managerial ownership on the disclosure of financial statements This study includes a quantitative descriptive study, which reveal the size of the influence between variables expressed in figures. The population in this study is a real estate company listed on the Indonesia Stock Exchange in 2010-2014. The research sample of 10 companies during the fifth period, in order to get a  sample  of  15  taken  by  purposive  sampling  technique.  The  data  used  is secondary data taken with engineering documentation. This research testing methods through multiple linear regression analysis with SPSS 20. The results showed the simultaneous measurement company and managerial ownership affect the disclosure of financial statements. Partially size significantly influence the company's financial statement disclosure and managerial    ownership    affect    the    disclosure    of    financial    statements.The conclusions of this research is only the size of the company having a significant effect on the disclosure of financial statements. Suggestions for further research about to conduct similar research in order to add a sample in which the unit of analysis in this study is not only on the type of real estate that research produced can be better than the previous research.  Keywords: company size, managerial ownership, financial statement disclosure